Screen Time During the Coronavirus (Covid-19) Pandemic is Related to the Developmental Status of Preschoolers - Sugiarti Sugiarti; Sunarsih Sunarsih; Dedek Saiful Kohir (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT The Covid-19 pandemic that preschoolers have faced for the past 2 years has caused children to stay at home for a long time and be exposed to more screen time. This study aims to determine the effect of screen time during the Covid-19 pandemic on the developmental status of preschool-aged children. This study used a cross-sectional analytic design with 60 mothers and their children aged 4-6 years (preschool). Samples were taken using a purposive sampling technique that met the inclusion criteria. This study used a screen time questionnaire, Developmental Pre Screening Questionnaire (KPSP), and a visual acuity test examination (TDL). Data were analyzed using univariate analysis and Chi-Square bivariate analysis. The results showed that the majority of children had a total screen time of 56.7% in the high category. Chi-square analysis showed that there was a significant relationship between children's screen time and developmental screening results (p-value = 0.001) and visual status (p-value = 0.005). Children with high screen time (≥ 2 hours/day) have a 22 times greater chance of experiencing doubtful development (OR = 22), and a 15.48 times greater chance of experiencing visual impairment (OR = 15.48) compared to children with low screen time (< 2 hours/day). This study recommends that parents limit screen time to no more than 2 hours per day for preschool-aged children because it can affect their developmental status. Keywords: Screen time; Preschool; Covid-19; Child Development